The role of brand commitment and brand attachment on repurchase intention of SMEs product during post Covid-19 pandemic era - Jasin, Mochammad (International Journal of Social and Management Studies, 2022)
This study aims to analyze the effect of brand attachment on repurchase intention with brand commitment as an intervening variable on customers. This research method is a quantitative method. The type of non-probability sampling technique used in this study is purposive sampling where the researcher will choose the respondent who best fits the research criteria. Snow-ball sampling technique through social media was also used in this study. Data analysis in this study was obtained from data obtained by researchers through the distribution of research instruments or questionnaires to 250 SMEs owner respondents which were then processed using the Partial Least Square (PLS) method with the SmartPLS 3.0 software tool. The results of this study prove that brand commitment has a positive and significant effect on repurchase intention, brand attachment has a positive and significant effect on repurchase intention, brand commitment has a positive and significant effect on brand attachment. consumer attachment and commitment to repurchase intention, the brand can influence the repurchase behavior of the brand.